Mediation in Pakistan-India Conflict: Potential and Constraints: Exploring the Potential and Constraints of Mediation in the Pakistan-India Conflict (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Precursor variables-conditions and possibilities under which a particular relationship or phenomenon is most likely to happen are very significant. Such social, psychological, political and historical variables constitute the all-embracing context decisive the nature and outcomes of a phenomenon. The effectiveness of mediation depends as such upon these background factors as on the interests and resources of the parties and the mediator. In the light of antecedent conditions and contextual factors, this paper evaluates how far Pakistan-India conflict advances itself to resolution through third-party intervention. We shall examine the arguments on the relevance of mediation, and then see in what way these contextual factors help or hinder third-party role in Pakistan-India conflict.